Post-activation depression of the Hoffman reflex is not altered by galvanic vestibular stimulation in healthy subjects - Alvarado-Navarrete, Mónica del Carmen; Pliego-Carrillo, Adriana C.; Ledesma-Ramírez, Claudia Ivette; Cuellar, Carlos A. (Frontiers in Integrative Neuroscience, 2023)
The comprehension of the neural elements interacting in the spinal cord affected by vestibular input will contribute to the understanding of movement execution in normal and pathological conditions. In this context, Hoffman's reflex (H-reflex) has been used to evaluate transient excitability changes on the spinal cord descending pathways. The post-activation depression (P-AD) of the H-reflex consists of evoking consecutive responses (>1 Hz) provoking an amplitude depression, which has been shown to diminish in pathological conditions (i.e., spasticity, diabetic neuropathy). Galvanic Vestibular Stimulation (GVS) is a noninvasive method that activates the vestibular afferents and has been used to study the excitability of the H-reflex applied as a conditioning pulse. To our knowledge, there are no reports evaluating the P-AD during and after GVS. Our primary aim was to determine if GVS alters the P-AD evoked by stimulating the tibial nerve at 0.1, 1, 5, and 10 Hz, recording in the gastrocnemius and soleus muscles. Direct current stimulation of 2.0 ± 0.6 mA with the cathode ipsilateral (Ipsi) or contralateral (Contra) to the H-reflex electrode montage was applied bilaterally over the mastoid process in 19 healthy subjects. The P-AD's immediate post-GVS response (P Ipsi, P Contra) was also analyzed. Secondarily, we analyzed the excitability of the H-reflex during GVS. Responses evoked at 0.1 Hz with GVS, post-GVS, and a Control (no GVS) condition were used for comparisons. Our results show that P-AD persisted in all subjects despite increased excitability induced by GVS: statistical significance was found when comparing P-AD at 1, 5, and 10 Hz with the corresponding condition (Control, Ipsi, P Ipsi, Contra, P Contra) at 0.1 Hz (p <0.001). Additionally, the increase in excitability produced by GVS was quantified for the first H-reflex of each P-AD stimulation frequency. The 2 This is a provisional file, not the final typeset article percentage change for all GVS conditions surpassed the Control by at least 20%, being statistically significant for Contra compared to Control (p <0.01). In summary, although GVS increases the excitability of the vestibulospinal pathway at a premotor level, the neural inhibitory mechanism present in P-AD remains unaltered in healthy subjects.